1990
DOI: 10.1093/bja/64.1.59
|View full text |Cite
|
Sign up to set email alerts
|

Anticonvulsant Properties of Propofol and Thiopentone: Comparison Using Two Tests in Laboratory Mice

Abstract: Experiments were carried out in mice to assess the protection provided by thiopentone (Intraval, May and Baker) and propofol (Diprivan, I.C.I.) against epileptiform seizures induced by electroshock and pentylenetetrazol. Intraperitoneal administration of propofol 50 mg kg-1 and thiopentone 25 mg kg-1 produced similar peak behavioural effects of mild sedation and incoordination. However, at these doses propofol afforded a greater degree of protection against pentylenetetrazol than thiopentone and at greater dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
2
1

Year Published

1992
1992
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(48 citation statements)
references
References 4 publications
5
40
2
1
Order By: Relevance
“…8). There is conflicting data in the literature concerning proconvulsant (DeFriez and Wong, 1992;Cochran et al, 1996) versus anticonvulsant effect of propofol (Lowson et al, 1990;De Riu et al, 1992). Indeed, adverse effects of propofol have been observed in man at induction of anesthesia and its termination before awaking, indicating that the proconvulsant effect of propofol occurs at low blood concentrations (Smith et al, 1996).…”
Section: __________________________________________________________ Ementioning
confidence: 99%
“…8). There is conflicting data in the literature concerning proconvulsant (DeFriez and Wong, 1992;Cochran et al, 1996) versus anticonvulsant effect of propofol (Lowson et al, 1990;De Riu et al, 1992). Indeed, adverse effects of propofol have been observed in man at induction of anesthesia and its termination before awaking, indicating that the proconvulsant effect of propofol occurs at low blood concentrations (Smith et al, 1996).…”
Section: __________________________________________________________ Ementioning
confidence: 99%
“…9~ Experiments carried out in rodents to assess the protection afforded by propofol and thiopentone against induced epileptiform seizures showed that both anaesthetic drugs were effective at sedative doses. 92,93 In an animal model of induced status epilepticus, bolus administration of propofol followed by an infusion completely suppressed electrical and clinical seizures in rabbits. This suggests that propofol may be useful in patients with status epilepticus when other agents have failed.…”
Section: Cerebral Physiology and Metabolismmentioning
confidence: 99%
“…In rodents, propofol inhibits seizures induced by electroshock, i.v. pentylenetetrazol (Lowson et al, 1990) and i.v. lidocaine (Lee et al, 1998).…”
Section: Sl Peterson Et A! /Neurotoricology 25 (2004) And85-847mentioning
confidence: 99%